What Lines, Rats, and Sheep Can Tell Us - Taylor, Alex (Design Issues, 2017)
Alex S Taylor (2017) What Lines, Rats, and Sheep Can Tell Us, Design Issues 3(3), p. 25-36, pdf, doi:10.1162/DESI_a_00449 In his Research Through Design provocation, Tim Ingold invites his audience to think with string, lines, and meshworks. In this article, I use Ingold’s concepts to explore an orientation to design, one that threads through both Ingold’s work and Vinciane Despret’s vivid and moving accounts of human-animal relations. This is a thinking and doing through design that seeks to be expansive, that looks to expand the capacities of humans and non-humans in relation to one another.